Effect of marc pressing and geographical area on Sangiovese wine quality. (January 2020) - Rinaldi, Alessandra; Louazil, Philippe; Iturmendi, Nerea; Moine, Virginie; Moio, Luigi
Abstract: Sangiovese is one of the most widespread grape cultivar in Italy. Owing to Sangiovese's ability to take on characteristics of region, climate and those imparted by the winemaker, wines made from this grape vary widely in colour and flavour. In this study, we evaluated the effect of marc pressing on polyphenolic and sensory quality of Sangiovese wines from different areas of Tuscany. 100% Sangiovese grapes were elaborated according to the same protocol obtaining 8 free-run and press wines. Polyphenolic analyses comprised: colour parameters, pigmented polymers, anthocyanins, tannins, flavans, phenolic compounds (HPLC-MS), phloroglucinolysis. Sensory analysis (astringency intensity and subqualities, taste, odor, aroma) was carried out by a trained jury. The effect of marc pressing depended on native phenolic compounds and on geographical area. Furthermore, wines from the same area showed a high variability. In general, press wines showed less colour, pigmented polymers, flavonols, and more flavan-3-ols. Pressing showed an influence on sensory characteristics related to astringency subqualities and aroma. Free-run wines were perceived as more acid, less adhesive, hard, aggressive, and characterized by soft tannins and full aroma than press wines. Indeed, the aroma of Sangiovese free-run wines had an important pool of odorants able to produce fruity and balsamic notes. Highlights: Differences between free-run and press Sangiovese wines were determined. The effect of geographical area on polyphenols is more pronounced than pressing. Free-run wines are characterized by a higher percentage of prodelphinidins and flavonols. The marc pressing affects the astringency subqualities and aroma of Sangiovese. Free-run wines are perceived as less aggressive, greener, richer, and fully aromatic.